VUV absorption spectroscopy of bacterial spores and DNA components. (18th October 2016) - Fiebrandt, Marcel; Lackmann, Jan-Wilm; Raguse, Marina; Moeller, Ralf; Awakowicz, Peter; Stapelmann, Katharina
Abstract: Low-pressure plasmas can be used to inactivate bacterial spores and sterilize goods for medical and pharmaceutical applications. A crucial factor are damages induced by UV and VUV radiation emitted by the plasma. To analyze inactivation processes and protection strategies of spores, absorption spectra of two B. subtilis strains are measured. The results indicate, that the inner and outer coat of the spore significantly contribute to the absorption of UV-C and also of the VUV, protecting the spore against radiation based damages. As the sample preparation can significantly influence the absorption spectra due to salt residues, the cleaning procedure and sample deposition is tested for its reproducibility by measuring DNA oligomers and pUC18 plasmid DNA. The measurements are compared and discussed with results from the literature, showing a strong decrease of the salt content enabling the detection of absorption structures in the samples.